The role of mass media in political life - Nugaraitė, Audronė (Information & Media, 1996)
The role of mass media in political life is discussed in the article. Knowledge and information acquire real power in modern society. For this reason, the press, radio, and television that have become the most important spreaders of knowledge and information claim to rise from the fourth position in the hierarchy of power to the first one. The largest part of our knowledge concerning reality is related to the messages of mass media. The article deals with the functions of mass media and the effect that they have on the audience. The issues of mass media ownership (dependency) are mentioned. The monopolization of information, followed by limitations, restrains personal freedom as well as right to choose. It often happens that the press that by its very nature should express the public interest, turns to means of political pressure that offend human dignity and honor. Hundreds of cases concerned with the offense to human dignity and honor in the press and electronic media testify to the existence of this delicate modern problem.